A Path Forward for Regenerative Medicine: Navigating Regulatory Challenges. Issue 4 (3rd August 2018) - Fanaroff, Alexander C.; Morrow, Valarie; Krucoff, Mitchell W.; Seltzer, Jonathan H.; Perin, Emerson C.; Taylor, Doris A.; Miller, Leslie W.; Zeiher, Andreas M.; Fernández-Avilés, Francisco; Losordo, Douglas W.; Henry, Timothy D.; Povsic, Thomas J.
Abstract : Although clinical trials of cell-based approaches to cardiovascular disease have yielded some promising results, no cell-based therapy has achieved regulatory approval for a cardiovascular indication. To broadly assess the challenges to regulatory approval and identify strategies to facilitate this goal, the Cardiac Safety Research Consortium sponsored a session during the Texas Heart Institute International Symposium on Cardiovascular Regenerative Medicine in September 2017. This session convened leaders in cardiovascular regenerative medicine, including participants from academia, the pharmaceutical industry, the US Food and Drug Administration, and the Cardiac Safety Research Consortium, with particular focus on treatments closest to regulatory approval. A goal of the session was to identify barriers to regulatory approval and potential pathways to overcome them. Barriers identified include manufacturing and therapeutic complexity, difficulties identifying an optimal comparator group, limited industry capacity for funding pivotal clinical trials, and challenges to demonstrating efficacy on clinical end points required for regulatory decisions. Strategies to overcome these barriers include precompetitive development of a cell therapy registry network to enable dual-purposing of clinical data as part of pragmatic clinical trial design, development of standardized terminology for product activity and end points to facilitate this registry, use of innovative statistical methods and quality of life or functional end points to supplement outcomes such as death or heart failure hospitalization and reduce sample size, involvement of patients in determining the research agenda, and use of the Food and Drug Administration's new Regenerative Medicine Advanced Therapy designation to facilitate early discussion with regulatory authorities when planning development pathways.